Role perceptions and role expectations of principals, counselors, and teachers in relation to guidance services in the secondary and elementary schools, Division of Manila City Schools - Cruz, Helen A. 1936- (s.n.], 1965)
This study investigates the role perceptions and role expectations of principals, guidance counselors, and teachers. The survey method of study through a parallel checklist was used as the basic method of study. Findings reveal that principals in the secondary and elementary levels perceived themselves performing administrative and service functions; guidance counselors perceive having guidance and counseling functions; teachers were perceived as having instructional functions.